The influence of chronic periodontitis and type 2 diabetes mellitus on resistin levels of gingival crevicular fluid- a systematic review and meta-analysis - Dax Abraham; Alpa Gupta; Arun Kumar Duraisamy; Mrinalini Mrinalini (Journal of Oral Biology and Craniofacial Research)
Aim: Chronic periodontitis (CP), a prevalent inflammatory dental disease, has been linked to systemic conditions like Type 2 Diabetes Mellitus (T2DM). This systematic review and meta-analysis aimed to evaluate resistin levels in the Gingival Crevicular Fluid (GCF) of CP individuals with T2DM. The objective was to determine if resistin could be a potential biomarker for periodontal disease in T2DM individuals. Methods: The review included data from seventeen clinical studies that investigated resistin levels in GCF of individuals diagnosed with CP and T2DM. Data were sourced from PubMed, Scopus, and EBSCOhost, selected for their extensive coverage of medical and dental research, ensuring thorough retrieval of relevant studies. From the initial seventeen studies, five complied with the strict inclusion criteria for meta-analysis. Results: Using a comprehensive meta-analysis, the significance of GCF Resistin levels in individuals with CP and T2DM relative to the healthy groups was examined. In addition, a meta-analysis was carried out to look into the relationship between periodontal probing depth (PPD) and CP and T2DM. The results indicated that individuals with T2DM and CP had significantly higher GCF resistin levels than the other groups. Furthermore, the PPD in T2DM with CP was significantly greater than in the other groups. Conclusion: The present review highlights the potential role of resistin as a biomarker to diagnose individuals with chronic periodontitis and T2DM. Clinical significance: The significantly elevated levels of resistin suggest that resistin could serve as a potential biomarker for T2DM in individuals with CP. This could lead to improved methods of early diagnosis and treatment, which could enhance individual outcomes and quality of life. Prospero registration: The registration number CRD42023467186.